(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Tinnitus is a prevalent symptom of many illnesses. A particular tinnitus may be caused by nasopharyngeal lesions, however the origin is usually unclear. Here, we describe a case of nasopharyngeal inverted papilloma in which the only initial symptom is rustling tinnitus. The tympanic membrane was undamaged, and the impedance audiometry and hearing test results were normal. Sonotubometry, however, revealed that the Eustachian tube was completely blocked. The nasopharynx was occupied by a big tumor that started in the choana and made a rustling sound when she spoke or swallowed. After this tumor was removed, the tinnitus completely disappeared. As far as we know, this case’s tumor origin and presenting symptom are extremely uncommon, and a nasopharyngeal examination is necessary to diagnose unidentified hearing complaints.